2017
DOI: 10.1016/j.jallcom.2017.09.255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe content, sintering temperature and powder processing on the microstructure, fracture and mechanical behaviours of Ti-Mo-Zr-Fe alloys

Abstract: The present work studies the effect of iron on the microstructural characterization and mechanical properties of Ti12Mo6ZrxFe alloys that fabricated by two different techniques elemental blend (EB) at 600 MPa and mechanical alloying (MA) at 600 MPa and 900 MPa with different sintering temperatures. The Ti12Mo6ZrxFe (x = 1, 2, 3 and 4 wt.%) alloys were investigated to develop new biomedical materials used for dental implant application. The microstructure, residual porosity and the mechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
4
15
0
1
Order By: Relevance
“…For quaternary alloys like Ti-12Mo-6Zr-3Fe; β-phases reaches almost 100%. Average β-phases decreased with higher % of Fe with elemental blend techniques and from EDX analysis; it is also confirmed the good distribution of alloying element from my previous paper (Mohan et al, 2017). Due to solubility of alloying element in Zr, the alloy Zr-12Mo-xTi have equiaxed β crystal grain can be observed (Nie et al, 2014).…”
Section: Chapter 5: Discussion Of the Resultssupporting
confidence: 81%
“…For quaternary alloys like Ti-12Mo-6Zr-3Fe; β-phases reaches almost 100%. Average β-phases decreased with higher % of Fe with elemental blend techniques and from EDX analysis; it is also confirmed the good distribution of alloying element from my previous paper (Mohan et al, 2017). Due to solubility of alloying element in Zr, the alloy Zr-12Mo-xTi have equiaxed β crystal grain can be observed (Nie et al, 2014).…”
Section: Chapter 5: Discussion Of the Resultssupporting
confidence: 81%
“…Chaves et al [15] explored the microstructural properties and mechanical behavior of b-type Ti-(10, 15, and 25)Nb-3Fe alloys and reported that Ti-25Nb-3Fe alloy exhibited improved phase stability and the lowest Young's modulus (65 GPa). Mohan et al [16] produced Ti-12Mo-6Zr-xFe (x = 1, 2, 3, and 4) alloys by P/M and reported that additions of small amounts of Fe improved the b-phase stability. Apart from structural and mechanical properties, biological response of cast Ti-5Nb-xFe (x = 0, 1, 2, 3, 4, and 5) alloys was investigated by Hsu et al [17] where all studied alloys were reported as biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of each alloy plays a decisive role in its final mechanical properties. Both Nb and Mo have a strong β-stabilizing effect on Ti alloys, but Mo appears to increase mechanical characteristics to a greater extent than Nb [17,18]. The variability in flexural strength data is decomposed into statistically significant contributions due to Mo content, relative density, and grain size, as depicted in Figure 12.…”
Section: Discussionmentioning
confidence: 99%